Bis(2-amino-6-methylpyridinium) tris(pyridine-2,6-dicarboxylato)zirconate(IV) dihydrate - Pasdar, Hoda (International Union of Crystallography, 2011)
In the title compound, (C(6)H(9)N(2))(2)[Zr(C(7)H(3)NO(4))(3)]·2H(2)O, the Zr(IV) atom is nine-coordinated by three pyridine-2,6-dicarboxylate ligands in a distorted tricapped trigonal–prismatic ZrN(3)O(6) environment. The crystal packing is stabilized by intermolecular N—H⋯O and O—H⋯O hydrogen bonds.